Implementing language politeness to strengthen students' character in elementary schools - Romadhoni Shiddiqi Hidayatullah; Irfai Fathurohman; Nur Fajrie; Sri Surachmi W (Indonesian Journal of Educational Development (IJED), 2026)
Politeness in language plays an important role in encouraging social behavior and character development in elementary school students. However, previous research has focused solely on the value of linguistic politeness from a linguistic perspective, without considering its contribution to character education. This research addresses this gap by analyzing how language politeness practices encourage character development in elementary school students and identifying strategies to strengthen character education. This case study research was conducted in three elementary schools in Jepara Regency, Central Java, Indonesia, with a sample of 5th-grade students, class teachers, and school principals. Researchers selected participants using purposive sampling based on their active involvement in language politeness and character education programs. Researchers collected data through classroom observations, semi-structured interviews, and document analysis using observation sheets, interview guides, and documentation checklists. The researchers analyzed the data using the interactive model from Miles, Huberman, and Saldaña, supported by open coding, thematic analysis, and triangulation to ensure reliability. The findings indicate that politeness in classroom interactions, teacher modeling, and daily communication practices can enhance students' discipline, respect, empathy, responsibility, and social awareness. The results offer a new perspective by showing that linguistic politeness serves as an integrated pedagogical strategy for character education, not just linguistic competence. The findings also offer practical implications for teachers and school leaders in designing classroom practices that foster positive communication and character values.